2017
DOI: 10.1002/app.45710
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked poly(vinyl alcohol) composite films with cellulose nanocrystals: Mechanical and thermal properties

Abstract: In this work, poly(vinyl alcohol) (PVA) and cellulose nanocrystals (CNCs) were crosslinked using sodium tetraborate decahydrate (borax) to improve the mechanical and thermal properties of the neat PVA. The results showed that the CNCs affected the crystallization behavior of the crosslinked PVA. The crystallization temperature of the crosslinked PVA with CNCs increased considerably from ∼152 to ∼187 °C. The continuous improvement of the thermal stability was observed with the increasing content of CNCs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 42 publications
(101 reference statements)
1
24
0
Order By: Relevance
“…The 0 CNC-F samples showed a value of 16.3% for moisture uptake after 120 h. The moisture uptake was slightly reduced to 15.6 % with the addition of 1 wt% CNCs. Similar decrease of moisture uptake with the presence of CNCs in PVA films has been recently reported [19]. This reduction of moisture uptake was due to less amounts of freely hydroxyl groups of both PVA and CNCS interacted with water.…”
Section: Resultssupporting
confidence: 86%
“…The 0 CNC-F samples showed a value of 16.3% for moisture uptake after 120 h. The moisture uptake was slightly reduced to 15.6 % with the addition of 1 wt% CNCs. Similar decrease of moisture uptake with the presence of CNCs in PVA films has been recently reported [19]. This reduction of moisture uptake was due to less amounts of freely hydroxyl groups of both PVA and CNCS interacted with water.…”
Section: Resultssupporting
confidence: 86%
“…The observed physical properties of MCS-b-PVA film are presented in Table 2. The resulting data is revealing the Recently, researchers [38,39] have been optimized the maximum stress and elastic modulus with variation of cellulose contents in PVA matrix. Pereira et al [40] have been reported that addition of 3% cellulose filler in PVA does not improve its mechanical properties significantly.…”
Section: Physical Characterization Of Filmmentioning
confidence: 95%
“…From the same group, there is a study on mechanical and thermal properties of crosslinked poly (vinyl alcohol) composite films with cellulose nanocrystals [66]. Crosslinker for the system was sodium tetraborate decahydrate (borax), and different weight % of CNCs was added to the PVA matrix.…”
Section: Nanocellulose-pva Crosslinkingmentioning
confidence: 99%